Application of pre-fabricated geopolymer permanent formworks (PGPFs): A novel approach to provide durability and mechanical strength of reinforced concrete. (January 2022) - Dehkordi, Erfan Riahi; Ramezanianpour, Ali Akbar; Moodi, Faramarz
Abstract: Permanent formworks (PFs) are elements which remain after construction for various applications including improving strength parameters or thermal and acoustic insulation. In aggressive coastal environments, the quality of concrete may decrease due to difficult operating conditions. In this research, a novel application of PFs for enhancing the durability of concrete structures is discussed. To begin with, important evaluation criteria were set for the PFs. Thanks to the desirable properties, a suitable geopolymer mixture was selected to make PFs. Hence, mechanical and durability performance of the samples were examined by several experiments. Subsequently, the connection means between the formwork and the substrate (conventional concrete) were studied by pull-off and Bi-surface experiments. In this way, various treatments were carried out on the surface of the PFs to ensure a suitable bond in the joints. At last, boundary between the PFs was found as a threat to the penetration of chloride ions. So that, different adhesives were applied to seal the PFs borders to finally suggest the desired option. The findings of this study indicate that the approach of using prefabricated PFs can be effective in ensuring the durability of reinforced concrete structures, especially against chloride ions penetration. The mechanical properties of the structure can also be improved with the help of PFs. The use of polyurethane mastic is recommended to protect the seam between the PFs and also the surfaces indentation through a (square) lattice as well as ridging the squares are suggested options for better connection of PFs to the substrate. Highlights: Using the permanent formwork can improve the durability as well as the mechanical properties of the concrete structure. Achieving a suitable geopolymer mixture to make a permanent formwork is possible with the help of various experiments. Connection of the formworks with each other and with the substrate is the important factor in the permanent formwork system.